FENOMENA DISKRIMINASI DALAM ANTOLOGI CERPEN ‘YANG LEBIH BIJAK DARIPADA PERI’ KARYA RIZQI TURAMA - Wahid, Muhammad Aqil (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Rizqi Turama's anthology of short stories ‘Yang Lebih Bijak daripada Peri’ presents interesting stories related to social phenomena that occur in society. The aim of this research is to identify and describe the reality of discrimination and its impact on the lives of the characters in the short story anthology 'Yang is wiser than fairies' by Rizqi Turama. The type of this research is qualitative descriptive research. The data collection technique used was reading short stories and then the data found and identified were recorded. Based on the research conducted, researchers found two forms of discrimination that existed in the story. These discriminations take the form of: direct discrimination which includes social status discrimination, age discrimination and class discrimination. Apart from that, discrimination also comes in the form of indirect discrimination which comes in the form of establishing the status quo. Researchers also found several impacts caused by discrimination, including: loss of work commitment, physical and mental health and loss of freedom of speech.